AB0334 Musculoskeletal ultrasonography assists the diagnostic performance of the 2010 classification criteria for rheumatoid arthritis. (23rd January 2014) - Kawashiri, S.-Y.; Suzuki, T.S.; Okada, A.; Yamasaki, S.; Tamai, M.; Nakamura, H.; Origuchi, T.; Uetani, M.; Aoyagi, K.; Eguchi, K.; Kawakami, A.
Abstract : Background: Recent imaging modalities such as musculoskeletal ultrasonography (MSKUS) and magnetic resonance imaging (MRI) are known to detect joint injury very frequently in early arthritis patients. Objectives: To investigate whether MSKUS assists the diagnostic performance of the 2010 rheumatoid arthritis (RA) classification criteria comparing its usefulness with plain MRI. Methods: Sixty-nine early arthritis patients were consecutively enrolled from May 2010 through February 2011. None of the patients had beentreated with disease-modifying antirheumatic drugs (DMARDs) including biologics or glucocorticoids. In MSKUS of bilateral wrist and finger joints including the 1st–5th metacarpophalangeal (MCP) joints, the 1st interpharangeal (IP) joint and the 2nd–5th proximal interpharangeal(PIP)joints, the findings obtained by gray scale (GS) and power Doppler (PD) assessment were graded on a semi-quantitative scale from 0 to 3. Plain MRI of both wrist and finger joints was also examined. The diagnosis of RA was defined by the initiation of DMARDs within the first 3 months. The diagnostic performanceof the patients was evaluated at entry using the 2010 RA classification criteria in conjunction with MSKUS or MRI. Results: The mean disease duration, age, prevalence of RF and anti-cyclic citrullinated peptide antibodies (ACPA) at examination were 3.9 months, 54 years-old, 46.3% and 36.2%, respectively. The 2010 RA classification criteria classified RA at a sensitivity of 59.5%, a specificity of 87.5%, and a positive predictive value (PPV) of 84.6%. The best MSKUS finding for differentiating RA was the presence of a PD grade ≥2 that was superior to MRI-proven osteitis. We have proposed that the decision tree algorithm of the 2010 RA classification criteria with a PD grade ≥2 reveals the best discriminative ability. Conclusions: MSKUS, especially with a strong PD signal, is very useful to assist the diagnostic performance of the 2010 RA classification criteriain the early recognition of RA. References: Kawashiri SY, et al. The power Doppler ultrasonography score from 24 synovial sites or 6 simplified synovial sites, including the metacarpophalangeal joints, reflects the clinical disease activity and level of serum biomarkers in patients with rheumatoid arthritis. Rheumatology (Oxford) 2011; 50: 962-5. Disclosure of Interest: None Declared